2012
DOI: 10.1371/journal.pone.0031311
|View full text |Cite
|
Sign up to set email alerts
|

A Synthesis of Tagging Studies Examining the Behaviour and Survival of Anadromous Salmonids in Marine Environments

Abstract: This paper synthesizes tagging studies to highlight the current state of knowledge concerning the behaviour and survival of anadromous salmonids in the marine environment. Scientific literature was reviewed to quantify the number and type of studies that have investigated behaviour and survival of anadromous forms of Pacific salmon (Oncorhynchus spp.), Atlantic salmon (Salmo salar), brown trout (Salmo trutta), steelhead (Oncorhynchus mykiss), and cutthroat trout (Oncorhynchus clarkii). We examined three catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
118
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 170 publications
(205 reference statements)
5
118
0
Order By: Relevance
“…While not done in our study, it would also be possible to batch-tag stocked fish (e.g., with coded wire tags, visible implant tags, or fluorescent marking) to support differentiation from wild fish, although it would only be sensible if all stocked fish are marked, with the choice of tag, cost, and efficiency variable dependent on the size of the fish being stocked as well as the expected recovery methodology (Drenner et al, 2012). While not entirely new, recent developments in otolith marking show increased promise for such questions, as the natural differences in water chemistry between rivers and hatcheries should provide a natural mark in otoliths that allow distinction between hatchery and wild fish-albeit individuals must be sacrificed to retrieve the information (Barnett-Johnson et al, 2008).…”
Section: Other Tagging Programsmentioning
confidence: 99%
“…While not done in our study, it would also be possible to batch-tag stocked fish (e.g., with coded wire tags, visible implant tags, or fluorescent marking) to support differentiation from wild fish, although it would only be sensible if all stocked fish are marked, with the choice of tag, cost, and efficiency variable dependent on the size of the fish being stocked as well as the expected recovery methodology (Drenner et al, 2012). While not entirely new, recent developments in otolith marking show increased promise for such questions, as the natural differences in water chemistry between rivers and hatcheries should provide a natural mark in otoliths that allow distinction between hatchery and wild fish-albeit individuals must be sacrificed to retrieve the information (Barnett-Johnson et al, 2008).…”
Section: Other Tagging Programsmentioning
confidence: 99%
“…Over 20 years ago, Baras [10] reviewed more than 1000 papers from studies using aquatic telemetry and found only 14 to evaluate the effects of external attachment of electronic tags on fish. In 2012, Drenner et al [11], reviewed tagging studies of salmonids in marine environments and commented on the lack of evaluations of tagging/handling effects. A generic problem in such evaluations is to disentangle the various effects of capture, handling, tagging, holding, and transporting wild fish.…”
Section: Introductionmentioning
confidence: 99%
“…Previous telemetry studies in other areas generally indicated that Chinook swam deeper in the water column than Sockeye when studies contrasted depth of migration, and generally moved more slowly (the latter possibly due in at least some studies to tagged Chinook being sexually immature and not undertaking strongly directed homing migrations) [20][21][22][23][24][25]. Drenner et al [26] summarized much of the telemetry literature by noting that '…vertical position in the water column in coastal areas can vary among species and even within species between relatively short distances on continental shelves' and noting that Sockeye '… choose different depths when swimming in well mixed versus stratified coastal waters' , and that '… several species continue to exhibit diel vertical movement patterns during this (that is, the adult) portion of their life'. In Cook Inlet, earlier attempts to identify differences in migration depth by evaluating the depth of fish capture in setnets [27] were considered unsuccessful in providing useful information.…”
Section: Introductionmentioning
confidence: 99%